Constraining sub-seasonal glacier mass balance in the Swiss Alps using Sentinel-2-derived snow-cover observations - Cremona, Aaron; id_orcid:0 000-0003-2553-903X; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Landmann, Johannes M.; Schwaizer, Gabriele; Paul, Frank; Farinotti, Daniel; id_orcid:0 000-0003-3417-4570 (Cambridge University Press, 2025)
The severe ice losses observed for European glaciers in recent years have increased the interest in monitoring short-term glacier changes. Here, we present a method for constraining modelled glacier mass balance at the sub-seasonal scale and apply it to ten selected glaciers in the Swiss Alps over the period 2015-23. The method relies on observations of the snow-covered area fraction (SCAF) retrieved from Sentinel-2 imagery and long-term mean glacier mass balances. The additional information provided by the SCAF observations is shown to improve winter mass balance estimates by 22% on average over the study sites and by up to 70% in individual cases. Our approach exhibits good performance, with a mean absolute deviation (MAD) to the observed seasonal mass balances of 0.28 m w.e. and an MAD to the observed SCAFs of 6%. The results highlight the importance of accurately constraining winter accumulation when aiming to reproduce the evolution of glacier mass balance over the melt season and to better separate accumulation and ablation components. Since our method relies on remotely sensed observations and avoids the need for in situ measurements, we conclude that it holds potential for regional-scale glacier monitoring. ISSN:0022-1430 ISSN:1727-5652